2016
DOI: 10.1590/2359-3997000000222
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between parameters of self-monitoring of blood glucose and the perception of health-related quality of life in patients with type 1 diabetes mellitus

Abstract: Objective: The aim of this study was to evaluate how different parameters of short-term glycemic control would correlate with the perception of health-related quality of life (HRQoL) in patients with type 1 diabetes mellitus (T1D). Subjects and methods: A total of 50 T1D patients aged 18 to 50 years were evaluated with the questionnaires Problem Areas in Diabetes (PAID) scale and Diabetes Quality of Life (DQOL) measure after 30 days of self-monitoring of blood glucose (SMBG). Glycemic control was evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
13
1
3
Order By: Relevance
“…SMBG is recognized as a valuable tool for diabetes management, having been demonstrated to help patients achieve better biological outcomes, 3-6,13,25-29 and to increase their disease self-awareness and improve on their management strategies, both at a clinical and lifestyle levels. 3,7-11,13,30-34 The results of this 6-month observational study show that SMBG via OneTouch blood glucose meter, with its characteristics, including its color-coded display and easy-to-understand results, contributes to helping not only to improve glycemic control but also to may lead to a better disease self-management.…”
Section: Discussionmentioning
confidence: 91%
“…SMBG is recognized as a valuable tool for diabetes management, having been demonstrated to help patients achieve better biological outcomes, 3-6,13,25-29 and to increase their disease self-awareness and improve on their management strategies, both at a clinical and lifestyle levels. 3,7-11,13,30-34 The results of this 6-month observational study show that SMBG via OneTouch blood glucose meter, with its characteristics, including its color-coded display and easy-to-understand results, contributes to helping not only to improve glycemic control but also to may lead to a better disease self-management.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, glycemic instability emerged as a female-specific factor which adversely affected QoL. Published data are not consistent with the association of QoL and metabolic control, assessed by HbA 1c levels [ 11 , 36 39 ], the standard method for assessing glycemic control. However, used as a sole marker of glycemic control, HbA 1c does not reflect intra- and interday glycemic excursions that may lead to hypoglycemia or hyperglycemia events.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have reported that because of the aversive nature of hypoglycemic episodes and the associated risk for harm thereof, individuals with T1D can develop a significant FOH, which can negatively affect their QoL. 17,30 Although some extent of fear can be considered appropriate and adaptive given the potential risk of hypoglycemia, it may become life-threatening and challenging for some patients. For these patients, FOH may cause great anxiety about diabetes management, obsessive self-monitoring, deliberate maintenance of high blood glucose levels, co-dependency, feelings of guilt and frustration, a perceived sense of loss of control, embarrassment, relationship stress, and avoidant behavior.…”
Section: Discussionmentioning
confidence: 99%